Exploring the Impact of Personal and Partner Traits on Sexuality: Sexual Excitation, Sexual Inhibition, and Big Five Predict Sexual Function in Couples. Issue 3 (24th March 2019) - Velten, Julia; Brailovskaia, Julia; Margraf, Jürgen
Abstract : Sexual difficulties are common among women and men and are associated with various mental and physical health problems. Although psychological traits are known to impact sexual attitudes and behavior, sexuality- and personality-related traits have not been jointly investigated to assess their relevance for sexual functioning in couples. The aim of this study was to investigate how psychological traits of two partners influence women's and men's sexual function. Data from 964 couples, representative of the adult population in Germany, were analyzed. Sexual function was assessed with the Female Sexual Function Index (FSFI) and the International Index of Erectile Function (IIEF). Sexuality-related traits were measured with the Sexual Excitation/Sexual Inhibition Inventory for Women and Men (SESII-W/M). Personality was measured with self-report and partner-rating versions of the Big Five Inventory (BFI). Sexual excitation was a positive and sexual inhibition was a negative predictor of sexual function in both genders. Women whose partners were sexually inhibited reported lower sexual function. Conscientious individuals reported better sexual function. Women whose partners were more conscientious also had better sexual function. Assessing partner-related factors may be helpful to identify predisposing and maintaining factors of sexual dysfunctions, especially in women.